Pola makan suku asli Papua dan non-Papua sebagai faktor risiko kejadian hipertensi - Sarni Rante Allo Bela; Bambang Djarwoto; I Made Alit Gunawan (Jurnal Gizi Klinik Indonesia, 2014)
Background: Hypertension is one of the problems in the medical and public health sector. The prevalence of hypertension in Jayapura City is 23,8%. Hypertensive disease was ranked 6th among the top 10 diseases in Abepura Hospital. The risk factors, a diet containing high fat, high sodium, low potassium and excessive alcohol consumption has contributed to the increasing of blood pressure.Objective: To determine the degree of hypertension difference between Papuans and non-Papuans, and the effect of intake of fat, sodium, potassium and alcohol consumption as risk factors for hypertension in each tribe.Method: The study was an observational analytic with a case-control design. Samples are 248 which is divided in 62 cases and 62 controls on each tribe. Data analysis using the statistical independent t-test, Chi-Square, Mantel Haenzel, Multiple Regression Logistic.Results: Non-Papuan tribes had 1.9 times higher risk of hypertension stage 2. The fat intake of indigenous Papuans (OR=3.250) and non-Papuans (OR=3.275) correlated significantly. Sodium intake significantly associated in indigenous Papuans, but the non-Papuans, have a significant relation (OR=2.531). There was a correlation between potassium intake in indigenous Papuans (OR=2.348), but the non-Papuans, was not. Consumption of alcohol in indigenous Papuans was significantly associated (OR=2.343), but the non-Papuans, was not. Multivariate analysis showed that psychosocial stress, consumption of alcohol, family history of hypertension, and potassium intake were contributing in indigenous Papuans. Intake of fat, sodium intake, and obesity was contributed in non-Papuan tribes. Conclusion: Non-Papuan tribes prone to has hypertension stage 2. In Papuans, fat intake (> 30%), potassium intake (<2000 mg) and excessive alcohol (≥ 2 glasses/day) are risk factors. In the non-Papuan, fat intake (> 30%) and sodium intake (≥ 2300 mg) are risk factors for hypertension.